A murine model of prurigo nodularis-like skin lesions induced by persistent scratching under type 2 inflammatory conditions - Wu, Jiali; Li, Xiahong; Huang, Siqi; Tang, Siyi; Zhang, Kaoyuan; Yan, Jiamin; Chen, Xiaofan; Dou, Xia (Frontiers in Immunology, 2025)
IntroductionPrurigo nodularis (PN) is a chronic inflammatory dermatosis characterized by robust pruritus and highly keratinizing nodules sympathetically distributed on the trunk and extensor sides of the limbs with an impact on quality of life and socioeconomic burden. To investigate the pathogenesis and develop novel therapeutic approaches, a preclinical animal model recapitulating the PN phenotypes is needed.MethodsWe constructed a novel PN-like mouse model by applying repetitive mechanical scratching in the context of type 2 inflammation. We utilized 6-8-week-old C57BL/6 mice for a 28 - day modeling study. The modeling protocol consisted of daily MC903 treatment plus 100 cell scraper scratches for the first 14 days, followed by alternate-day MC903 with continued daily scratching for the subsequent 14 days, with bandaging applied to prevent spontaneous scratching.ResultsHistological analysis of lesions revealed aberrant epidermal hyperplasia and differentiation, dermal fibrosis, inflammatory infiltration, angiogenesis, increased intraepidermal nerve fiber density, and enhanced nerve fiber sprouting. Immunological characterization revealed a mixed Th1/Th2/Th17/Th22 profile with a skewing toward Th17/Th22 polarization.ConclusionThis optimized model faithfully recapitulates the key clinicopathological features of PN patients, providing a robust preclinical platform for investigating disease mechanisms and evaluating potential therapeutics.